Integrating Student-Centered Approaches in Islamic Education: A Case Study of SMPN 1 Kadipaten, Indonesia - Tatang Muh Nasir; Mohammad Sabarudin; Yusuf Sugiana; Muhamad Yasir; Mahmud Mahmud; Pepen Supendi (AL-ISHLAH: Jurnal Pendidikan, 2026)
Islamic Religious Education (PAI) in secondary schools plays a crucial role in fostering students’ moral character, spiritual awareness, and social responsibility. Amid rapid digitalization and shifting adolescent values, there is a growing need for pedagogical approaches that emphasize the internalization of Islamic values through student-centered learning.This study employed a descriptive qualitative design conducted at SMPN 1 Kadipaten, Tasikmalaya Regency. Data were collected through classroom observations, in-depth interviews with PAI teachers, and a review of relevant literature. The data were analyzed using thematic analysis to identify patterns in learning approaches, strategies, methods, and instructional techniques.The findings indicate that PAI instruction consistently կիրառes a student-centered approach supported by three primary strategies: inquiry-based, collaborative, and contextual learning. Four dominant teaching methods—group discussion, role-playing, interactive questioning, and digital media integration—were regularly applied. Contextual techniques, including storytelling, Islamic-themed ice breaking, and authentic assessment, enhanced student engagement, motivation, and the internalization of values across cognitive, affective, and psychomotor domains.The integration of student-centered approaches with diverse strategies and contextual techniques significantly improves the effectiveness of PAI learning and supports Islamic character formation. These findings contribute empirical insights to contemporary discourse on Islamic and moral education, highlighting the importance of adaptive pedagogy in addressing current educational challenges.